Quality improvement: patient education for management of hypertension in pregnancy - Kriti M. Goel; Rose A. Maxwell; Morgan E. Cooley; Traci M. Rackett; Jerome L. Yaklic (Hypertension in Pregnancy, 2021)
Objective: To assess the effectiveness of interactive education tools for hypertension in pregnancy.Two interactive education tools were introduced. Methods: Pregnant women with hypertension completed questionnaires before (Pre-I) and after)Post-I) the intervention.Providers rated satisfaction and effectiveness of the education methods. Results: The Post-I group (N=45) showed slight improvement on both Perceived (4.5±0.7) and Actual knowledge (2.2 ± 1.0) compared to the Pre-I group (N=45; Perceived: 4.2±1.0; Actual: 1.7±1.3; p<.05) .Providers reported higher satisfaction after the intervention (2.6±1.1 vs 4.1±0.7; p <.001). iscussion: The intervention increased patients’ knowledge and providers rating of patient knowledge, and decreased the time needed for patient education.